Lithological controls on hydrogeochemical parameters: a case study from parts of Vaigai River basin, Madurai, India - Sharma, K. K.; Jayashree, S. (Journal of Nepal Geological Society, 1998)
Water being a universal solvent carries minerals in solution which though present in small quantities determine its suitability for various purposes. The suitability of a well is determined more by the quality of water and not by the quantity of water which it can yield. Geochemical studies provide complete know ledge of the water resources of a hydrological region. The influence of mineralogical composition upon the filtering properties and the water quality can be analysed form the point of view of the mineral properties. Quality of ground water varies from place to place and from stratum to stratum, it also varies from season to season. There are various techniques to analyse the groundwater quality. However, not much work has been carried out to study the variations in water quality as a result of 1ithological and structural controls. In the present paper, an attempt has been made in this direction. It is found that the first step for any groundwater quality data analysis should be its correlation with the lithological variations. This paper presents the details of the work carried out in the Vaigai River basin of Tamilnadu.